The Influence of Anxiety in Learning English for Specific Purposes on the Students for Non-English Department - Oktavia, Masitoh; Mulia, Vilya Lakstian Catra; Herawan, Doni (Allure Journal, 2025)
Many students in the non-English Department feel anxious while speaking in front of the classroom and it has become a never-ending issue up to now. Therefore, this research focuses on investigating how anxiety factors affect students' behavior during EFL instruction and how non-English-speaking students' beliefs contribute to the development of anxiety.Â  Descriptive qualitative case study method was employed with the subject of the research were 32 students from the 4th semester of Arabic Language Education and Islamic Education study program at the non-English Department of Walisongo Islamic State University of Semarang. The instruments were field observation, interview, questionnaire, and Focus Group Discussion. The research revealed that non-English students learning ESP English commonly experience two primary types of anxiety: confusion and sweating. These feelings often arise due to a lack of preparation before attending English classes. Anxiety is heightened when students feel unprepared in three key areas: grammar, pronunciation, and vocabulary mastery. In conclusion, students tend to feel anxious when they overthink the instructions or have to speak English in front of many peers. However, they feel more comfortable and engaged when lecturers create a joyful and positive classroom atmosphere. It is recommended that ESP students adopt strategies to manage their anxiety, including thorough preparation, relaxation techniques, positive thinking, seeking support from peers, and developing acceptance. Additionally, teachers should play an active role in reducing students' anxiety by fostering a supportive and encouraging learning environment.